Speaking Backwards in Tagalog - Gill, David (Journal of Modern Languages, 2017)
This study considers the structural affinity of Golagat with a variety of ludlings in diverse languages, demonstrating how ludlings may yield insights into grammatical theory and the grammars of particular languages. Speaking backwards in Tagalog shows how the playful creativity of Pilipino children, constrained by the exigencies or phonological theory, interacts with the grammar of Tagalog to give rise to a ludling of exceptional beauty.